From food fishing to exclusion zones: the territorial conflict between the traditional fishermen, the port enterprises and the environmental preservation in the Brazilian coast - Foeger, Tarcisio Jose (Geografares, 2018)
This article addresses the food issue as a fundamental principle of territorial autonomy involving traditional (artisanal) fishing communities. Discussing the issue related to the processes of deterritorialization articulated by the institution of fishing exclusion zones, resulting from the installation of coastal port complexes and the creation of new marine and conservation units. In this sense, the work discusses issues such as the autonomy of these groups and their insertion in the local geopolitics front of the decision-making mechanisms of territorial management, where the result, almost always, is the inhibition of the fishing activity and consequently the reduction of fishing. Where the reflexes of this process go beyond food and productive issues, but permeate other elements of territorial citizenship in its different dimensions.Keywords: fishing - food - territories.